Abundant interactions and feedbacks between aquatic deoxygenation and the other planetary boundaries suggest “unsafe” levels of oxygen loss with far‐reaching impacts - Erica M. Ferrer; Yassir A. Eddebbar; Shailja Gangrade; Lillian R. McCormick; Ariel K. Pezner; De'Marcus Robinson; Véronique Garçon; Kevin C. Rose; Lisa A. Levin (Limnology and Oceanography, 2026)
Oxygen is critical for nearly all life on Earth, including aquatic species that breathe dissolved oxygen in both freshwater and marine systems. The rapid, global, and anthropogenic loss of dissolved oxygen known as “aquatic deoxygenation” threatens life in these environments, the human communities that depend on them, and Earth system stability long‐term. Recognizing the important and increasingly widespread effects of aquatic deoxygenation, scientists have proposed that it be added to the planetary boundary framework, which is designed to capture the wider envelope of Earth‐system conditions that support a “safe operating space for humanity.” Here, we argue that the planetary boundary framework should include maintenance of Earth's aquatic ecosystems and thus dissolved oxygen conditions. We synthesize important, in some cases poorly understood, interactions and feedbacks that exist between deoxygenation and all nine of the established planetary boundaries. We find that aquatic deoxygenation interacts with and extensively modulates other boundary processes, including climate change, nutrient loading, biodiversity loss, and aerosol loading. Subsequently, we identify and describe four indicators that can be used to assess the status of aquatic deoxygenation and eventually define a global boundary for it within the framework. Given these interactions and current rates of oxygen loss, we argue that aquatic deoxygenation is approaching an “unsafe space,” with Earth‐system impacts that are likely to be irreversible in our lifetimes. We discuss the wider societal significance of this research, including applications to the framework, future analyses, policy‐making, and management.

Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

Marine Prosperity Areas: a framework for aligning ecological restoration and human well-being using area-based protections - Octavio Aburto-Oropeza; Valentina Platzgummer; Erica M. Ferrer; Catalina López-Sagástegui; Rocío de Guadalupe Abud Mirabent; América Ávalos Galindo; Fabio Favoretto; Alfredo Giron-Nava; Isabel Mendoza Camacho; Claudia Núñez Sañudo; Marisol Plascencia de La Cruz; Alejandro Robles (Frontiers in Marine Science, 2025)
Mechanisms for marine ecological protection and recovery, including area-based conservation tools like ‘Marine Protected Areas’ (MPAs) are necessary tools to reach the Aichi Target or the forthcoming 30x30 target set by the Kunming-Montreal Biodiversity Framework. However, full ecosystem recovery takes years to manifest and the idea that MPA protection alone will foster human well-being is frequently contradicted by socio-economic evidence. Therefore, a new framework for marine area-based conservation and ecosystem restoration that reconciles the discrepancies between ecological recovery and socio-economic growth timelines is needed to effectively meet global biodiversity conservation targets. We introduce the concept of ‘Marine Prosperity Areas,’ (MPpA) an area-based conservation tool that prioritizes human prosperity as opposed to passively relying on ecosystem recovery to catalyze social change and economic growth. This concept leverages a suite of tried-and-true community-based intervention and investment strategies to strengthen and expand access to environmental science, social goods and services, and the financial perks of the blue economy. This data-driven framework may be of interest to stakeholders who support traditional area-based conservation models, but also to those who have been historically opposed to MPAs or have been excluded from past conservation processes.

Sustainable transformation in the Latin American and Caribbean districts through the implementation of a qualitative methodology. Challenges and key aspects to be addressed - Silvia Soutullo; Jose Antonio Ferrer; Oscar Seco; Helena López; Maria Nuria Sánchez; Mario Jorge Vitale; Alba Liony Reyes; Erica Norma Correa; Lara De Diego (Journal of Cleaner Production, 2024)

Semiautomated approach focused on new genomic information results in time and effort-efficient reannotation of negative exome data - Alejandro Ferrer; Patrick Duffy; Rory J. Olson; Michael A. Meiners; Laura Schultz-Rogers; Erica L. Macke; Stephanie Safgren; Joel A. Morales-Rosado; Margot A. Cousin; Gavin R. Oliver; David Rider; Megan Williams; et al. (Human Genetics, 2024)

Self-governance mediates small-scale fishing strategies, vulnerability and adaptive response - Timothy H. Frawley; Blanca González-Mon; Mateja Nenadovic; Fiona Gladstone; Keiko Nomura; José Alberto Zepeda-Domínguez; Salvador Rodriguez-Van Dyck; Erica M. Ferrer; Jorge Torre; Fiorenza Micheli; Heather M. Leslie; Xavier Basurto (Global Environmental Change, 2024)

Overfishing Increases the Carbon Footprint of Seafood Production From Small-Scale Fisheries - Erica M. Ferrer; Alfredo Giron-Nava; Octavio Aburto-Oropeza (Frontiers in Marine Science, 2022)
Small-scale fisheries (SSFs) and the foods they produce are extremely important, contributing 25–50% of global seafood landed for direct consumption. In some cases, SSFs provide seafoods with an exceptionally low carbon footprint, but like all food, it is important to understand the factors that regulate that footprint in the face of increasing demand and a worsening climate-ecological crisis. We utilize long-term fisheries monitoring data from Northwest Mexico to generate novel stock assessments and, subsequently, test the relationship between underlying fishery biomass and fuel intensity observed among several motorized SSFs. Using fuel data from over 4,000 individual fishing trips, in combination with estimated biomass data for 19 regional stocks, we show that the fuel footprint per kilogram of seafood increases sharply as the stock’s underlying annual biomass ( B ) falls below its estimated biomass at Maximum Sustainable Yield ( B MSY ). We find an inverse relationship between B/B MSY and fuel intensity using a test for simple correlation between the two ( r = -0.44), a linear regression analysis ( R 2 adj. = 0.17), and a mixed-effects model with gear type, year, and genus modelled as random effects. These results indicate that efforts to end overfishing, rebuild fishery stocks, and/or minimize intensive fishing practices will help to decrease the carbon emissions generated by motorized wild-catch fishing. We anticipate that this study will contribute an important “missing link” to discussions on how best to secure climate-resilient fisheries and, ideally, help SSF stakeholders garner recognition and support for SSFs in this context.

Exploring Changes in Fishery Emissions and Organic Carbon Impacts Associated With a Recovering Stock - Angela Helen Martin; Erica M. Ferrer; Corallie A. Hunt; Katinka Bleeker; Sebastián Villasante (Frontiers in Marine Science, 2022)
International objectives for sustainable development and biodiversity conservation require restoring fish populations to healthy levels and reducing fishing impacts on marine ecosystems. At the same time, governments, retailers, and consumers are increasingly motivated to reduce the carbon footprint of food. These concerns are reflected in measures of the EU Common Fisheries Policy (CFP) and the CFP Reform Regulation, which highlighted a need to move from traditional single-stock management toward an ecosystem approach to fisheries management (EAF). Using publicly available landings and effort data combined with estimates of adult population biomass, we develop methods to explore the potential for lowering emissions intensity and impacts on organic carbon stocks through ending overfishing and rebuilding stocks. We use the recent recovery of European hake ( Merluccius merluccius ) stocks in the Northeast Atlantic as a case study. With a focus on the hake fisheries of France, Spain, and the United Kingdom, we compare 2008 and 2016 fishing years. We make an initial estimate of the influence of changing stock status on greenhouse gas emissions during the fishery phase from fuel use and investigate the potential disturbance of organic carbon in the ecosystem, specifically via identification of bottom trawling overlap with organic-rich muddy sediments, and directly on storage in hake biomass. Our findings indicate that recovery of the hake stock was associated with reductions in overall emissions intensity from fuel and proportional impact on hake populations, however, total emissions from both fuel and landings increased, as did likely disturbance of sedimentary organic carbon in surface sediments due to benthic trawling. Ultimately, the aims of this analysis are to further explore the climate impacts of fisheries and overfishing, and to inform development of EAF in the EU.

Entering Negotiations: Early-Career Perspectives on the UN Conference of Parties and the Unfolding Climate Crisis - Erica M. Ferrer; Leticia M. Cavole; Simona Clausnitzer; Daniela F. Dias; Tashiana C. Osborne; Rishi Sugla; Emma Harrison (Frontiers in Marine Science, 2021)
As the pressure to address the climate crisis builds, scientists must walk the line between research and activism. This was apparent at the 2019 United Nations (UN) Framework Convention on Climate Change – Conference of the Parties (UNFCCC – COP), the largest annual meeting to address the climate crisis via supranational policymaking. COP has convened annually since 1995 in effort to establish international agreements for the reduction of greenhouse gas emissions, and in 2015, was the launch pad for the UN Paris Climate Agreement (PCA). Here, we present our collective perspective as early-career researchers on COP, an institution that we believe plays a critical role in the future of our oceans. Given the current pledges from signatories to the PCA, Earth is expected to warm ∼3°C by 2100, with the majority of anthropogenic heat content stored throughout the ocean. For this reason, among others, we feel it is crucial for ocean scientists to have a baseline understanding of the negotiations unfolding at COP and within the UNFCCC. We also provide evidence that certain features/structures of COP formalize colonial hierarchies, marginalize certain groups, and threaten to perpetuate the drivers of the environmental crises we all face. Thus, we urge that the future of such gatherings include purposeful and self-reflective acts of restructuring the space they occupy, the solutions they advocate, and the ways in which power is distributed amongst participants. We balance our critique with examples of how this has already been successful at COP, particularly with respect to organizing around ocean-climate issues.